THE ROLE OF THE POLICE IN EARLY DETECTION OF RADICALISM AND TERRORISM - Jati, Meidika Dwiantara Putra (Jurnal Hukum Khaira Ummah, 2024)
The purpose of this study is to determine, review and analyze the Police scheme in early detection of radicalism and terrorism. In this writing, the author uses a normative legal method with research specifications in the form of descriptive analysis. Radicalism in Indonesia is always associated with political radicalism. Radical politics in Indonesia is always associated with Islamic radicalism, because of the social and historical review of politics in Indonesia. This caution is needed, because talking about radicalism will very easily connote fundamentalism, militancy or Islamism. By implication, early detection is related to the Intelligence work pattern in this case the Police have an Intelligence unit with all intermediary fields to carry out their functions as the essence of law enforcement. Intelligence detection is not an accusation that a particular organization or group is indoctrinated in radicalism or terrorism. However, with detection, characteristic data will be obtained, data on the beliefs held will be compiled. The mechanism of the Police in carrying out early detection or with the term prevention which is as an action to reduce radicalism and prevent acts of terrorism in order to realize national security through a soft approach and a hard approach.